Enacting social change on a major scale: the role of business - Henderson, Rebecca (Henry Stewart Talks, 2023)
Climate change, Individual-level action, Organization-level action, Political-level action, Objective research, Wealth disparity, Redistributive taxation, Money in politics, Research funding